The quintessence of protecting the honor and dignity of a National Police officer - S. H. Pevko (Law and Safety)
The article examines a topical issue related to the protection of the police officers’ honor and dignity. It has been comprehensively analyzed the objects of legal protection, namely the concepts of “honor” and “dignity”, in order to determine what exactly is being infringed upon. In addition, the article examines the legal act that previously regulated the issue of liability for violation of the honor and dignity of police officers, but today the relevant provision, which was previously contained in the Criminal Code of Ukraine, has been excluded.